THE TECHNOLOGY AS ALLIED IN HISTORY TEACHING AND YOUR MEMBERSHIP IN BASIC EDUCATION SCHOOLS - Goncalves da Silva, Hilda Maria [UNESP]; David, Celia Maria [UNESP]; Mantovani, Almir [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This research sought to learn the use of information and communication technologies in public basic education in the state of Sao Paulo, specifically in relation to the teaching of history. There has been a historical context defense of the use of these technologies in educational institutions. The survey of qualitative data on the use of these resources was to cut the city of Franca and with the participation of students in the fourth year of the History of UNESP-France. Is learned from the analysis that despite the extensive literature on the advantages of using technology to the teaching of history in basic education classes and also the strong defense in relation to the use of these resources by the Secretariat of Sao Paulo State Education; the practical reality of educational institutions still is rooted in an educational process that is restricted essentially the figure of the teacher and the textbook, or the learning of reference provided by the state.
Keywords: Education; Technology; Teaching activities